The Contribution ICT in the Tunisian Economic Growth - Asma Bouthour (Communications of International Proceedings, 2022)
This article examines the impact of communication and information technologies (TIC), on the economic growth, on the level of the Tunisian framework. Initially, we tried to make a sweeping of the literature on the theory and the concept of the economic growth. Indeed, and thanks to the ICT, we are in the presence of a new economy. In the second time, and an empirical framework, we will test even impact of these technology on the economic growth and thus on the productivity of the companies. For that we used, the E-views model. Our sample is consisted of the Tunisian companies of the financial sector, and our data were collected near the reports/ratios of the INSS.
Keywords: ICT; economic growth; SFA